2014
DOI: 10.1080/00220388.2014.940909
|View full text |Cite
|
Sign up to set email alerts
|

Households’ Willingness to Pay for Health Microinsurance and its Impact on Actual Take-up: Results from a Field Experiment in Senegal

Abstract: Community-based health insurance schemes (CBHIS) have been present in the region of Theis, Senegal, for many years. Yet, despite the benefits they offer, take-up rates remain low. This article measures the willingness to pay (WTP) for CBHIS premiums in such a context; our results highlight the role of income, wealth and risk preferences as determinants of WTP. We also provide an analysis of the predictive power of WTP on the actual take-up of insurance following our offering of membership to a sample of 360 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(59 reference statements)
1
6
0
Order By: Relevance
“…Our findings also help clarify the role of risk preference in CBHI uptake. In the literature, while Bonan et al (2014) showed that risk-averse heads of households had a higher willingness to pay for health microinsurance in Senegal, Bonan et al ( 2017 ) found that risk aversion did not influence uptake. Dercon et al (2019) showed that, surprisingly, risk aversion may be negatively associated with health insurance demand in settings where trust in insurance schemes is limited (due to misperceptions of product attributes).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also help clarify the role of risk preference in CBHI uptake. In the literature, while Bonan et al (2014) showed that risk-averse heads of households had a higher willingness to pay for health microinsurance in Senegal, Bonan et al ( 2017 ) found that risk aversion did not influence uptake. Dercon et al (2019) showed that, surprisingly, risk aversion may be negatively associated with health insurance demand in settings where trust in insurance schemes is limited (due to misperceptions of product attributes).…”
Section: Discussionmentioning
confidence: 99%
“…Binam et al (2002) state that household economic conditions have an influence on willingness to pay [3]. Research by Bendig and Arun (2012) and Bonan (2013) found that a large number of stairs with a high number of non-productive ages could influence the willingness to pay premiums. [4] This is because the composition of the age of the respondent family, which consists mostly of the productive age, has a lower risk of illness so that the needs or demands for health service needs are also lower.…”
Section: Discussionmentioning
confidence: 99%
“…Research by Bendig and Arun (2012) and Bonan (2013) found that a large number of stairs with a high number of non-productive ages could influence the willingness to pay premiums. [4] This is because the composition of the age of the respondent family, which consists mostly of the productive age, has a lower risk of illness so that the needs or demands for health service needs are also lower. However, Lofgreen et al (2008) asserted that the variable number of families can influence the perception of the willingness of the community to pay premiums.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of insurance, several articles empirically examine WTP in developing countries for crop insurance (see, e.g., Bulte et al, 2019; Freudenreich & Mußhoff, 2018; Wang et al, 2020), health insurance (see, e.g., Bonan et al, 2014; Delavallade, 2017), livestock insurance (see, e.g., Castellani & Vigan'o, 2017), different types of index and microinsurance in different parts of the world (see, e.g., Elabed & Carter, 2015), flood insurance (see, e.g., Botzen & Bergh, 2012), and weather insurance (see, e.g., Fraser, 1992; Musshoff et al, 2008). For developed countries, analyses of WTP for insurance tend to focus on public social systems.…”
Section: Literature Reviewmentioning
confidence: 99%